2006
DOI: 10.1107/s1744309106041649
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary crystallographic characterization of PrnB, the second enzyme in the pyrrolnitrin biosynthetic pathway

Abstract: Pyrrolnitrin is the active ingredient of drugs for the treatment of superficial fungal infections and was used as a lead structure for the development of fludioxonil. It is an effective agent for plant diseases caused by the fungal pathogen Rhizoctonia solani. Pyrrolnitrin is made in four steps, the second of which, catalyzed by PrnB, is a novel chemical rearrangement of 7-chlorotryptophan. PrnB was overproduced in Pseudomonas fluorescens (BL915) and well diffracting crystals were obtained of a triple cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Complex Structure of PrnB with Cyanide-As described previously, we used the triple Cys mutant of PrnB (C21S, C60S, and C185S) because it is fully functional but, unlike native protein, does not aggregate (13,20). Crystals of native PrnB were soaked in 6 mM KCN to produce a binary complex structure of PrnB and cyanide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex Structure of PrnB with Cyanide-As described previously, we used the triple Cys mutant of PrnB (C21S, C60S, and C185S) because it is fully functional but, unlike native protein, does not aggregate (13,20). Crystals of native PrnB were soaked in 6 mM KCN to produce a binary complex structure of PrnB and cyanide.…”
Section: Resultsmentioning
confidence: 99%
“…Structural Biology-His-tagged PrnB Cys mutant (C21S, C60S, or C185S) was overproduced in P. fluorescence BL915 ⌬ORF1-4 (deletion of the gene cluster of the pyrrolnitrin biosynthesis pathway), purified, and crystallized as previously described (13,20) with two modifications; 7 M sterile filtered hemin was supplemented to the growth medium to ensure full incorporation of heme (21), and 0.1 M Bistris buffer (pH 6.2-6.4) was introduced to the crystallization condition and enhanced reproducibility of crystallization. The use of cyanide required appropriate safety considerations.…”
Section: Methodsmentioning
confidence: 99%
“…Mass spectrometric analysis of the acetone extraction is consistent with the presence of heme b (peak at 615.95 nm; calculated 615.6 nm). Protein crystals were only obtained from the triple mutant protein and the details of the crystallization have been reported (15). The best results were obtained using with 1.5 μ l protein solution (16mg / ml 50mM Tris pH 7.5) plus 1.5 μ l of precipitant (0.22 M magnesium sulfate, 16 % w/v PEG 3350) irrespective of whether protein was incubated with tryptophan (as a saturated solution) or not.…”
Section: Methodsmentioning
confidence: 99%
“…174 The crystal structure of PrnB revealed this enzyme to be a member of the heme-dependent dioxygenase superfamily and suggested that a tryptophane peroxide is the primary oxidation product. 175,176 The Rieske N-oxygenase PrnD, which generates the nitro group, was biochemically characterized, [177][178][179] and hydroxylamine and nitroso analogs were identified as intermediates. 179 PrnF was established as an NADH-dependent reductase of PrnD.…”
Section: Plantsmentioning
confidence: 99%